Perceptions of Secretary Candidates in the Implementation of ASEAN Economic Community - susi lowati (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
Welcoming MEA is already implemented until 2017, supplies hardskills and softkills as secretary must be learned and mastered by secretaries so that they can compete in the world of work. The purpose of this study is as follows: To determine the extent of a candidate's knowledge of the ASEAN secretary and MEA; their perceptions of the Enforcement of MEAs, as well as their readiness to face the MEA.This study was a descriptive study. The population in this study was all students majoring in secretarial or office management are actively studying at the College / Diploma Program and the Polytechnic of Malang. The number of respondents as many as 50 people. The results of this study are the majority of respondents have a standard knowledge about ASEAN and MEA, while the MEA regarding preparedness is still the standard. Respondents' perceptions of the implementation of the majority of states agreed in 2016 MEA implementation of MEAs. The conclusions of this study are as follows: (1) The secretary .Calon majority have knowledge of standard / was about ASEAN and the MEA and have the readiness standard / moderate in the face of MEA, 2016. (2). Perception secretaries on the use of MEA 2016 states agree on a majority of the MEA. The authors suggest that secretaries should increase preparedness in the face of the MEA in 2016 to study foreign languages and keep up with technology.